Pengaruh Ekstrak Habbatussauda Nigella Sativa terhadap Status Gizi - Shelly Indri Yagi; Yesi Nurmalasari; Rakhmi Rafie (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; Nutritional status of a person, apart from being determined by the nutritional content of this food, is also determined by the amount and quality of nutritional intake. This increase in intake can be triggered by an increase in appetite for Black Seed (Nigella sativa.) Objectives; know the effect of Black Seed Extract (Nigella sativa) on Nutritional Status. Method; a purely experimental pre-and post-test study with a control group design. The samples used were 24 rats which were divided into 4 groups. Result; that there was a significant increase in the lee index in the KP 150 KP1 group (p = 0.021) and the 150 KP1 dose group and the positive KP group (0.02) there was no significant pulse. decreased APGAR score in the KP1 dose group of 150 (p = 0.092) and the dose group of 300 (p = 0.327). Conclusion; that there is an effect of Black Seed Extract (Nigella sativa.) on the APGAR Score of physical appearance.